2011
DOI: 10.1111/j.1365-2753.2011.01707.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical instruments: reliability and validity critical appraisal

Abstract: This critical appraisal tool will aid both the health care practitioner to critically appraise the relevant literature and researchers to improve the quality of reporting of the validity and reliability of objective clinical tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 9 publications
0
98
0
1
Order By: Relevance
“…The quality of the included studies was assessed using the critical appraisal tool by Brink and Louw (2012), which does not incorporate a quality score and the impact of each item needs to be considered individually. Since the presented analysis was a study of one-point test result examination, the following 5 items were found not applicable: testing of interrater reliability and blinding of raters to the test results, blinding of raters to their own prior findings, variation of the order of examination, evaluation of time period between reference standard and index test, and independence of reference standard and index test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the included studies was assessed using the critical appraisal tool by Brink and Louw (2012), which does not incorporate a quality score and the impact of each item needs to be considered individually. Since the presented analysis was a study of one-point test result examination, the following 5 items were found not applicable: testing of interrater reliability and blinding of raters to the test results, blinding of raters to their own prior findings, variation of the order of examination, evaluation of time period between reference standard and index test, and independence of reference standard and index test.…”
Section: Resultsmentioning
confidence: 99%
“…The methodological quality of the studies was assessed using the critical appraisal tool established by Brink and Louw (2012). The tool consists of 13 items assessing the quality of a study.…”
Section: Methodsmentioning
confidence: 99%
“…Despite findings of high to very high inter-observer and intra-observer reliability of measurement methods reported within the included studies, many used inappropriate statistical methods for reliability data analysis. Kappa statistics [45], rho [41] and Pearson's correlation coefficient [36,42,48] are suggested in literature to overestimate or underestimate reliability [26,29]. The ICC with 95 % confidence interval (CI) is considered the best statistical method for analysing reliability data [49].…”
Section: Methodological Considerations For Included Studiesmentioning
confidence: 99%
“…The CAT has been designed to improve the quality of reporting of studies of the validity and reliability of objective clinical tools [26]. In item 13, statistical power was considered in conjunction with the methods of statistical analysis [27].…”
Section: Critical Appraisalmentioning
confidence: 99%
See 1 more Smart Citation